Development Of Learning Models For Industrial Dressmaking At Fashion Technologi Vocational School - Karlina, Nadya; Hasanah, Uswatun; Doriza, Shinta (Department of Home Economics, Faculty of Engineering, Universitas Negeri Semarang, 2020)
The purpose of the research is to develop a project-based independent learning model in Vocational Fashion Technology. The research and development method Ã‚Â uses 10 steps from Borg and Gall. The results of the development Project Based Independent Learning (PBIL) models are accompanied by PBIL learning manuals for educators. The steps of implementing the PBIL model, namely determining the fundamental questions, compiling project planning, preparing a schedule, monitoring students and project progress, analyzing project results and evaluating experience. Learning activities consist of face-to-face, independent learning by Android-based learning media and monitoring by social media. Effectiveness test results indicate , learning by PBIL models, students easier to learn lessons (97%); students helped in solving problems (91%); increase studentsÃ¢â‚¬â„¢ courage to share opinions (85%); support students to work in a team(94%); motivate students to reach achievement (97%); students able to solve post test questions easier than before (97%); motivating students to complete tasks (97%); learning by PBIL model, students is closer to their teacher (97%).